Inconsistency of speech at the top : an analysis on the chairman and the CEO's financial narratives - Gomes, Sara de Oliveira Verdasca Pereira (2022)
The purpose of this study is to investigate the inconsistency of speech between the Chairman of the board of directors and the Chief executive officer (CEO) by examining key language characteristics on their financial narratives. We analyze the chairman statement and CEO review sections on the companies’ annual report considering a sample of firms listed on the London Stock Exchange (LSE). We examine and compare the readability, textual tone and the use of forwardlooking discourse. Our results on tone and forward-looking discourse confirm there is inconsistency of speech. Moreover, when considering firms with declining performance our findings are consistent with the CEO making use of impression management strategies. Results on readability differ according to the measure of readability being used. We therefore question the fit of our measures and the robustness of our findings.